Replacing performance status with a simple patient-reported outcome in palliative radiotherapy prognostic modelling. (November 2022) - Howdon, Daniel; van den Hout, Wilbert; van der Linden, Yvette; Spencer, Katie
Highlights: The inclusion of clinician-assessed performance status in prognostic tools restricts their use to specialist settings. We investigate the use of patient-reported outcome measures in replacing clinician-assessed performance status in prognostic models. Patient-reported outcome measures are likely to be at least as useful in prognostic modelling as clinician-assessed performance status. Larger, more contemporaneous datasets, with broader patient populations are needed to confirm these results and the acceptability of this approach to patients and clinicians. Abstract: Background and purpose: Prognostication is key to determining care in advanced incurable cancer. Although performance status (PS) has been shown to be a strong prognostic predictor, inter-rater reliability is limited, restricting models to specialist settings. This study assessed the extent to which a simple patient-reported outcome measure (PROM), the EQ-5D, may replace PS for prognosis of patients with bone metastases. Materials and methods: Data from 1, 011 patients in the Dutch Bone Metastasis Study were used. Cox proportional hazards models were developed to investigate the prognostic value of models incorporating PS alone, the EQ-5D SC dimension alone, all EQ-5D dimensions and EQ–VAS, and finally all dimensions and PS. Three prognostic groups were identified and performance assessed using the Harrell's C-index and Altman-Royston index of separation. Results: Replacing performance status (PS) with the self-care (SC) dimension of the EQ-5D provides similar model performance. In our SC-based model, three groups are identified with median survival of 86 days (95 % CI 76–101), 174 days (95 % CI 145–213), and 483 days (95 % CI 431–539). Whilst not statistically significantly different, the C-index was 0.706 for the PS-only model, 0.718 for SC-only and 0.717 in our full model, suggesting patient-report outcome models perform as well as that based on PS. Conclusion: Prognostic performance was similar across all models. The SC model provides prognostic value similar to that of PS, particularly where a prognosis of<6 months is considered. Larger, more contemporaneous studies are needed to assess the extent to which PROMs may be of prognostic value, particularly where specialist assessment is less feasible.